Membangun Generasi Cerdas Berhukum - Arief Wahyudi (Universitas Medan Area, 2017)
Law has a strong relationship with humans and affects human life at all times. In this context the law is presented for human beings to fulfill the various interests in the social relations between humans, so that human intervention becomes the dominant factor in determining the erect or the collapse of the law. This is where the necessary intelligence of punishment is, how a nation interpret its own law and make itself an integral part of the legal system it embraces and in this context also a smart generation of law needs to be built. The role of building the intelligent generation of punishment can be done by students as a youth element that has strategic values supported by elements in the learning process and its role in social dynamics of society. The challenge for students is to educate their own penalties before educating the public in general.